1999
DOI: 10.1177/070674379904400508
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Rating of Compliance in Chronic Hemodialysis Patients

Abstract: A ssessing and measuring patient compliance is assuming increasing importance in clinical practice. Noncompliance has been shown to be a common cause of relapse in many conditions, for example, in bipolar patients on lithium (1), depressed subjects on antidepressants (2), schizophrenia patients on neuroleptics (3,4), and nephrology patients who have received a kidney transplant (5). It has been found that around 50% ofgeneral medical patients (6), 50% ofpsychiatric patients (3), and an average of 33% of hemodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The results indicate moderate to strong positive correlations between frequency and degree of nonadherence behavior for diet and fluid restrictions. These study results are consistent with reports from other research groups (Bame et al, 1993; Kimmel et al 2000; Mai et al, 1999). By using both indicators, additional approaches could be designed to identify patients at risk for continuous nonadherence behavior, as well as for “holiday nonadherers.”…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results indicate moderate to strong positive correlations between frequency and degree of nonadherence behavior for diet and fluid restrictions. These study results are consistent with reports from other research groups (Bame et al, 1993; Kimmel et al 2000; Mai et al, 1999). By using both indicators, additional approaches could be designed to identify patients at risk for continuous nonadherence behavior, as well as for “holiday nonadherers.”…”
Section: Discussionsupporting
confidence: 94%
“…When operational definitions are inconsistent, validity and reliability cannot be documented. Different approaches include the measurement of nonadherence according to demographic characteristics (Bame et al, 1993; Kaplan, DeNour, & Czaczkes, 1974; Leggat et al, 1998), psychological and behavioral variables (Kimmel et al, 1995; Kimmel et al, 1998; O'Brain, 1990), lab values (Arici et al, 1999; Block, Hulbert‐Shearon, Levin, & Port, 1998; Mai, Busby, & Bell, 1999), and comorbid conditions (Kaveh & Kimmel, 2001; Leggat et al, 1998). Demographic characteristics associated with nonadherence include racial group differences (Bame et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Being married was an important factor in nonadherence to diet and fluid restriction. Conversely, a Canadian study of 48 patients showed no significant relationship between marital status and adherence measures (Mai, Busby, & Bell, 1999). We did not find any other study on the relationship between marital status and treatment adherence in patients receiving HD.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐adherence with medications is also a problem in this population group (Laidlaw et al. 1999, Mai et al. 1999, Rahman & Griffin 2004) and can result in dietary deficiencies, hypertension and fluid overload.…”
Section: Introductionmentioning
confidence: 99%
“…Denhaerynck et al (2007) found that non-adherence in terms of shortening treatments ranged from 7-32% whilst that of skipping dialysis sessions ranged from 0-35%. Non-adherence with medications is also a problem in this population group (Laidlaw et al 1999, Mai et al 1999, Rahman & Griffin 2004 and can result in dietary deficiencies, hypertension and fluid overload. Lastly, non-adherence with dietary and fluid restrictions ranges from 20-78% (Lee & Molassiotis 2002, Durose et al 2004, Kugler et al 2005.…”
Section: Introductionmentioning
confidence: 99%